2021
DOI: 10.1093/hmg/ddab288
|View full text |Cite
|
Sign up to set email alerts
|

Mycndeficiency underlies the development of orofacial clefts in mice and humans

Abstract: Non-syndromic cleft lip with or without cleft palate (NSCL/P) is the most common subphenotype of non-syndromic orofacial clefts (NSOFCs) arising from genetic and/or environmental perturbations during embryonic development. We previously identified 2p24.2 as a risk locus associated with NSCL/P in the Chinese Han population, and MYCN is a candidate risk gene in this region. To understand the potential function of MYCN in craniofacial development, we generated Wnt1-Cre;Mycnflox/flox mice that exhibited cleft pala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This link was reinforced by the association of this locus with various cleft lip/palate traits (Extended Data Fig. 3e), for which MYCN deficiency is a known risk factor 26 . 27…”
Section: Resultsmentioning
confidence: 89%
“…This link was reinforced by the association of this locus with various cleft lip/palate traits (Extended Data Fig. 3e), for which MYCN deficiency is a known risk factor 26 . 27…”
Section: Resultsmentioning
confidence: 89%
“…Cranial neural crest cells (NCCs) are a migratory cell population and give rise to the majority of cartilage, 4 bone, 5 connective tissue and sensory ganglia 6 during craniofacial development. According to the most commonly reproduced version, auricle tissue is derived from NCCs that migrate into the first and second branchial arches.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, mice lacking Brca1 gene in the neural crests showed craniofacial abnormalities such as defective nasal‐frontal bones and smaller maxillary and mandibular bones (Kitami, Kitami, Kaku, Wang, & Komatsu, 2018). Knocking out Mycn in CNCCs could lead to the failure in palatal shelves elevation (Yang et al, 2022). Interference of SF3B2 resulted in disrupted formation of cranial neural crest precursor and subsequent craniofacial cartilage defects in Xenopus (Timberlake et al, 2021).…”
Section: Introductionmentioning
confidence: 99%